The Effects of Person–Organization Fit and Turnover Intention on Employees’ Creative Behavior: The Mediating Role of Psychological Ownership - Ucar, Ahmet Cengiz; Alpkan, Lutfihak; Elci, Meral (SAGE Publications, 2021)
Some recent studies have examined the behavioral antecedents of employees’ creative behavior. However, the potential role of psychological ownership is rarely taken into consideration. This study specifically examines the mediating role of psychological ownership in the relationship between person–organization (P–O) fit and turnover intention on the one hand and employees’ creative behavior on the other via a survey in Turkish organizations. Findings based on the data from 969 employees in Istanbul and Western Anatolia indicate that P–O fit is positively related and turnover intention negatively related to both psychological ownership and creative behavior, and that psychological ownership plays a full mediating role in these relations. Psychological ownership has a central role in employees’ creative behavior; it should thus be augmented together with its antecedents if managers wish to foster creative behaviors among their employees.
Keywords: AZ20-999; Social Sciences; History of scholarship and learning. The humanities